Weakly Approximaitly Quasi-Prime Submodules And Related Concepts - Mohammadali, Haibat K.; Mahmood, Shahad J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Let R be  commutative Ring , and let T be  unitary left .In this paper ,WAPP-quasi prime submodules are introduced as  new generalization of Weakly quasi prime submodules , where  proper submodule C of an R-module T is called WAPP â€“quasi prime submodule of T, if whenever 0â‰ rstÏµC, for r, s ÏµR , t ÏµT, implies that either  r tÏµ C +soc   or  s tÏµC +soc  .Many examples of characterizations and basic properties are given . Furthermore several characterizations of WAPP-quasi prime submodules in the class of multiplication modules are established.